Pertumbuhan dan Kelulushidupan Ikan Gabus (Channa striata) yang Diberi Pakan Maggot BSF (Hermetia illuences) - I Made Angga Wahyu Dinata; Pande Gde Sasmita Julyantoro; Ni Putu Putri Wijayanti (Bumi Lestari Journal of Environment, 2023)
Aquaculture is the fastest growing food production sector in the world. Snakehead fish (Channa striata) is one of the freshwater fish commodities in Indonesia which is still widely cultivated. Snakehead fish (Channa striata) is a fish that is economically feasible and has benefits that are beneficial to human health. This research was conducted in a period of 58 days aimed to determine the effect of feeding maggot BSF (Hermetia illuences) on the growth and survival of snakehead fish (Channa striata). The stocking density of fish in this study was 20 fish/pond, 3-4 cm in size fish obtained from cultivators in the Denpasar area, the pond used was made of tarpaulin with a size of 50×50 cm. This research used 3 treatments, treatments A (100% pellet), treatment B (100% BSF maggot), and treatment C (50% pellet + 50% BSF maggot) with 3 replications. Parameters observed in this study were specific growth rate, absolute length growth, survival rate, feed conversion ratio and water quality. The results of the research that have been carried out show that treatment C gave the highest yield on the specific growth rate, absolute length growth and survival rate of snakehead fish (Channa striata). The results of water quality measurements show that the temperature ranges from 29.32-30.18oC, pH values ??range from 6.50-5.52, and DO ranges from 2.79-2.90 mg/L, the water quality value is still in the optimum value range for maintenance of snakehead fish (Channa striata).